Characterizing the Potentials of Alcaligenes sp. for Acrylamide Degradation (Journal of Biochemistry, Microbiology and Biotechnology, 2023)
Microorganisms play a crucial role in the detoxification and elimination of harmful substances from the environment. Acrylamide is a major pollutant in soil from the breaking down of pesticide addictive. Slowly but steadily, the used of microbe-mediated acrylamide breakdown as a bioremediation approach has gained attention all around the world. This research was aimed to characterize the potential of previously isolated bacteria for acrylamide degradation. In this research five previously isolated bacteria were screened on minimal salt media (MSM) to assess their potential for utilizing acrylamide as the sole nitrogen source. Of all the isolates, isolate D, identified as Alcaligenes sp., displayed the highest growth on acrylamide supplemented MSM agar medium. The optimum conditions for acrylamide degradation by this bacterium were acrylamide concentration of 600 mg/L, pH 7.0, an inoculum size of 400 µL, an incubation time of 96 h, glucose concentration of 4 g/L and temperature of 35 oC. The ability of this isolate to convert toxic acrylamide into less harmful form is a novel finding, highlighting its significance as a valuable tool for bioremediation of this pollutant.